Capital Structure Policy in Property, Real Estate and Building Construction Sector Companies: Do Women Play a Role? - Fildza Alifa Balqis; Syahrun Nizar Maulana Muttaqin; Wulan Daniyati; Setiawan Setiawan (Indonesian Journal of Economics and Management, 2022)
The existence of women in the top management of companies is an issue in corporate governance. This study examines the influence of female directors, female commissioners, and female audit committees on capital structure (DER). This research is a type of quantitative research. The population in this study are property companies listed on the Indonesia Stock Exchange (IDX) and issuing annual reports for 2020. There are 73 research samples. The results of this study explain that female directors and female commissioners have a negative and insignificant effect on capital structure (DER). Meanwhile, the audit committee has a positive and insignificant effect on capital structure (DER). Due to the limitations of testing variables, company and year in this study, it is suggested that further researchers conduct tests with more varied variables, using more than one company and year so that the results obtained are more descriptive and accurate.